Cost of Patients With Hemophilia A and High-Titer Inhibitors in Colombia (2019)
Background: In Colombia, hemophilia is considered a high-cost disease, and hemophilia A with high-titer inhibitors may be responsible for a significant economic pressure on the Colombian health system. Objectives: To estimate the direct cost of care for patients with hemophilia A with high-titer inhibitors in Colombia, from the perspective of the health system. Methods: A cost-of-illness study was carried out using standard case methodology, which was designed based on literature review and validation by expert consensus. Scenarios were established for adults and children, including cases of prophylaxis, immune tolerance induction, bleeding, and surgery. The frequencies were taken from the official report for Colombia, issued by the HighCost Account 2017 (reported 2018). The prices were obtained from the list of regulated medicines in the country. The cost estimate is presented with a range of values by weight (between 10 kg and 90 kg).Results: The total estimated cost per year for Colombia was US $44 905 252 (between US $32 260 497 and US $58 202 393). The average cost per year calculated for a patient was US $498 947 (between US $358 450 and US $646 693). A total of 99.8% of the estimated cost was directly related to the cost of the coagulation factors and bypassing agents. Conclusions: Hemophilia A with high-titer inhibitors is a disease that generates significant pressure on the Colombian health system, mainly linked to the cost of factors and bypassing agents.